THE IMPROVEMENT OF KAMPONG AS AN INSTRUMENT TO MITIGATE FLOODS IN SURABAYA - Sarkawi B. Husain (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
The improvement of kampong –a residential area Inhabited mostly by thelower classin a town or city - was one of the efforts to prevent flood in the city of Surabaya. The effortwas not only related to its contribution to minimize the flood butit also hadmany aspects. The serious attention to kampong improvement from the Dutch colonial government only appeared in the second decade of the 20th century. When the city of Surabaya wasoccupied byJapanese troopsfrom March 8th, 1942 untill the independence revolution, the attention tothe kampong improvementstopped and many kampongs were destroyed bythe war. An effort to restore them resumed in 1950s when everything retuned to normal. To intensify the program of kampong improvement, the W.R. Supratman projectwas launched following the establishment of Kampong Improvement Project (KIP). One of the criteria to determine a kampong that needed to be restored is whether itwas always flooded or not. Nevertheless, the kampong improvementdidnot really solve the flood problem thoroughly. However, anevaluation shows that this project has madea significant contribution to minimizing the flood in the city of Surabaya.